Consequences of COVID-19 Lockdown on Children and Their Pets: Dangerous Increase of Dog Bites among the Paediatric Population - Giovanni Parente; Tommaso Gargano; Marco Di Mitri; Sara Cravano; Eduje Thomas; Marzia Vastano; Michela Maffi; Michele Libri; Mario Lima (MDPI AG, 2021)
Background: The SARS-CoV-2 pandemic has not only put our national health systems to the test, but it also notably hit the economy, the society and the psychology of the people. Our pets have been subjected to the pandemic related stress too. The aim of the study was to evaluate whether the stress induced on domestic dogs resulted in an increase of dog bites in the paediatric population. Methods: A retrospective study was conducted on all patients admitted to our paediatric emergency department for dog bite from January 2014 and December 2020. We compared the total mean dog bites of the years 2014-2019 and the mean number per single month with the respective 2020 data. The bites were divided between bites from family dogs and bites from stranger dogs. Continuous data were analysed using single sample t test while categorical values with chi-squared test, considering statistically significant a p value < 0.05. Results: From January 2014 to December 2019, we recorded a mean of 41 ± 5.9 dog bites (range: 30-46) of which a mean 13 ± 2.6 (range: 10-17) were due to family dogs (32%) and a mean of 28 ± 2.4 (range: 25-31) were due to stranger dogs (68%); the male-to-female ratio was 3:2 and 43% of the injuries concerned the head and face, 26% the lower limbs, 25% the upper limbs, 3% the genitalia and 3% the torso. From January 2020 to December 2020, 30 children were admitted for dog bites: 22 were from family dogs (73%) and 8 from stranger dogs (27%); the male-to-female ratio was 14:11 and 72% of the injuries concerned the head and face, 16% the upper limbs, 8% the lower limbs and 4% the torso. The 2020 data's higher number of family dog bites compared with the mean of those in the 2014-2019 period was statistically significant (p < 0.01) such as the 2020 data's lower number of stranger dog bites when compared with the mean number of stranger dog bites in the 2014-2019 period (p < 0.01). Between 2014 and 2019, a mean of 9 ± 2 (range: 6-12) of the wounds needed to be sutured (22%), while 32 ± 3 (range: 28-35) wounds were discharged after application of Steri Strips (78%). On the other hand, in 2020, 21 wounds needed to be sutured (70%), and 9 received just Steri Strips application (41%). The frequency distribution of the treatments required (stitches vs. Steri Strips) between the 2014 to 2019 period and the 2020 period was statistically significant (p < 0.0001). Conclusions: The number of family dog bites in children increased in 2020, especially during the lockdown period. Paediatricians should pay a lot of attention now more than ever to educate parents on the importance of always supervising children who are playing with dogs.